All Screen‐Printed, Polymer‐Nanowire Based Foldable Electronics for mm‐Wave Applications. Issue 11 (26th July 2021) - Li, Weiwei; Zhang, Haoran; Kagita, Srujana; Shamim, Atif
Abstract: With the surge in devices for Internet of Things (IoT) applications, there is great interest in flexible electronics to be mass manufactured at lower costs. Screen‐printing is well‐known for mass manufacturing, however, this method has mostly focused on printing metallic patterns. Rare efforts have been devoted to print substrates for high frequency (mm‐wave) electronics, which requires low dielectric loss to ensure a decent system efficiency. This paper presents a novel screen‐printable composite ink comprising of acrylonitrile‐butadiene‐styrene and ceramic particles, through which, dielectric substrates with various thicknesses (down to few microns), lateral dimensions, and relative permittivities can be printed. A low dielectric loss of 0.0063 at 28 GHz (fifth generation (5G) communication band) makes the substrates suitable for mm‐wave electronics. A custom silver nanowires based screen‐printable ink is utilized for metallic printing to provide high conductivity (3.4 × 106 S m ‐1 ) and stable electrical response under bent or folded conditions. As a proof of concept for fully printed mm‐wave electronics, a flexible quasi‐Yagi antenna operating at 5G band (26.5–29.5 GHz) is demonstrated that exhibits decent performance in flat as well as bent conditions, confirming the suitability of the material system and printing processes for mass production of IoT and wearable electronics. Abstract : A screen‐printable polymer–ceramic composite ink is developed to create dielectric substrates on demand. The printed substrates demonstrate smooth surface and low dielectric loss, which are beneficial for mm‐wave application. Silver nanowires help to provide stable performance under deformable conditions. A foldable antenna operating at fifth generation communication band is realized through this all‐screen‐printing process.